Familial association of polycystic ovary syndrome (PCOS) in women attending the gynaecological endocrinology clinic at Groote Schuur Hospital - Edelstein, Sascha (Department of Obstetrics and Gynaecology, 2014)
Includes bibliographical references (leaves 60-65).